COMPUTERIZED ADMINISTRATIVE SYSTEM CHECK-IN AND CHECKOUT HOTEL GUEST KUSUMA MADYA AMBARAWA - Mohd. Firman Batubara; Sahni D Purba, Skom, MM (Jurnal Sistem Informasi, 2001)
Thesis entitled "Computerized System Administration check-in and Check-out GuestOn Kusuma Hotel Madya Ambarawa" had been conducted in March-April 2000.The objective is to process administrative data check-in and Check-out Guest at HotelKusuma Madya Ambarawa rapid, accurate, and up to date at any time. The writing ofthis study were made to the administrative processing of check-in and check-outguests can take place quickly and without error.Research methodology is included field studies and literature studies. Meiputifieldwork observations, and interviews. While the literature study conducted by theresearch literature relevant to the problem.After a global design was completed, then can be found with the design ofadministrative systems bahw check-in and check-out room, a lot of manual work thatcan be eliminated and administrative control process to check in and check-out gueststo be more rapid, precise yet efficient.